PERANCANGAN RENCANA STRATEGIS SISTEM INFORMASI DAN TEKNOLOGI INFORMASI (SI/TI): STUDI KASUS STMIK XYZ - Maryani, Maryani; Darudiato, Suparto (Bina Nusantara University, 2010)
Nowadays, business activity in every organization will not be parted from information system (IS) and information technology (IT). STMIK XYZ is one private college that has a good business growth. In order to reach the objective of the college in its vision and mission, it needs business strategy and IS/IT strategy. The basic concept in arranging framework IS/IT strategic planning in STMIK XYZ is John Ward and Joe Peppard’s concept. The framework of IS/IT strategic planning consists of 5 steps, that are initialization preparation strategic planning of IS/IT, understanding business and information needs, defining target of IS/IT, defining strategic IS/IT, and planning and implementation. Strategic analysis uses PEST analysis method, BCG matrix analysis, five Porter power analysis, SWOT analysis, value chain analysis, CSF and KPI analysis. The research result is to make a framework of IS/IT integrated strategic planning so it could ease the management to manage resources to produce information that needed, accurate, and could be used by anybody.Keywords: planning, business strategy, IS/IT strategy, information system strategic planning, Ward & Peppard method.